A LEGAL REVIEW BETWEEN IMPACTS OF CHILD SEXUAL ABUSE AND CRIMINAL COMPENSATION ORDER IN MALAYSIA - Izmi Izdiharuddin B Che Jamaludin Mahmud; Nadzriah Ahmad; Rafizah Abu Hassan (Journal of Islamic, Social, Economics and Development, 2022)
In Malaysia, child sexual abuse issues ("CSA") is prevalent even during the Covid-19 pandemic. In addition, there are numerous social and health issues against child sexualabuse victims ("CSA victims") as it is associated with short and long-term impacts on daily life.Therefore, the compensation may practically assist CSA victims in redressing their sufferings.The primary legislation towards restoring victims' loss or injuries in the Malaysian criminaljustice system derives from section 426 (1A) of the Criminal Procedure Code. This provisionallows criminal courts to order the offenders to pay a criminal compensation order ("CCO")to victims subject to the application by the public prosecution. Nevertheless, there areshortcomings in the application of Section 426 (1A) due to various reasons, such as the offenderdoes not have the financial ability to pay the compensation, lack of implementation of victims'rights in the criminal justice system, oversight of legal principle of CCO by governmentappointedstakeholders and the system rigidity in the assessment of CCO. Thus, this paperfocuses on the relationship between the impacts and availability of compensation for childsexual abuses cases in Malaysia. This research adopts the doctrinal legal research method andwill determine whether there is a compensatory justice legal system for CSA victims inMalaysia.